Piriformis Injection: An Ultrasound-Guided Technique - Bardowski, Elizabeth A. (Arthrosc Tech, 2019)
Piriformis syndrome is an elusive condition that likely is overlooked and overdiagnosed in equal proportions. Image-guided injection of the muscle is an essential element in the assessment and management of this disorder. Ultrasonography allows visualization of the anatomy of the piriformis and its relation with the sciatic nerve. Ultrasound-guided injection of the muscle can be performed in an effective, reproducible fashion and, with careful attention to the details of the procedure, can be performed with minimal morbidity to the patient. This method has the advantage of being exceptionally well tolerated by the patient and can be performed in the office with minimal patient inconvenience and the opportunity for a real-time assessment of the patient's response to the injection. Our ultrasound-guided technique of piriformis muscle injection is detailed in this article.